2019
DOI: 10.1002/ange.201814266
|View full text |Cite
|
Sign up to set email alerts
|

Selective Engineering of Linkage‐Specific α2,6‐N‐Linked Sialoproteins Using Sydnone‐Modified Sialic Acid Bioorthogonal Reporters

Abstract: The metabolic oligosaccharide engineering (MOE) strategy using unnatural sialic acids has recently enabled the visualization of the sialome in living systems.However,MOE only reports on global sialylation and dissected information regarding subsets of sialosides is missing. Described here is the synthesis and utilization of sialic acids modified with asydnone reporter for the metabolic labeling of sialoconjugates.T he positioning of the reporter on the sugar significantly altered its metabolic fate.Further in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Introduction of the sydnone moiety onto sialic acid demonstrated that the chemical reporter significantly altered the metabolic fate of the studied sugar. While Neu5SydCl was not metabolically incorporated into cell‐surface sialoconjugates, Neu9NSydCl was well tolerated by the glyco‐biosynthetic machinery of the cell [39] . By employing an in vitro enzymatic‐ 1 H‐NMR coupled assay, we identified CMP‐sialic acid synthetase, the enzyme responsible for the activation of sialic acid into its cytidine monophosphate‐analogue, as the enzymatic roadblock for the biosynthesis of sialoglycans with the Neu5SydCl precursor [39] …”
Section: Exploiting Sydnone 13‐dipoles As Chemical Reporters For Cont...mentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction of the sydnone moiety onto sialic acid demonstrated that the chemical reporter significantly altered the metabolic fate of the studied sugar. While Neu5SydCl was not metabolically incorporated into cell‐surface sialoconjugates, Neu9NSydCl was well tolerated by the glyco‐biosynthetic machinery of the cell [39] . By employing an in vitro enzymatic‐ 1 H‐NMR coupled assay, we identified CMP‐sialic acid synthetase, the enzyme responsible for the activation of sialic acid into its cytidine monophosphate‐analogue, as the enzymatic roadblock for the biosynthesis of sialoglycans with the Neu5SydCl precursor [39] …”
Section: Exploiting Sydnone 13‐dipoles As Chemical Reporters For Cont...mentioning
confidence: 99%
“…This strategy implies that the unnatural sugar must traverse biosynthetic pathways, thus requiring the chemical reporter to be structurally minimally invasive [38] . Despite the many attractive features of employing azido‐sugars for the MOE, and notably its inconspicuousness, we recently showed that azides can be reduced into amines in biological systems by the action of endogenous thiols, potentially leading to the formation of undesired metabolites [39] . Having recently identified sydnones as highly stable chemical reporters for the imaging of modified‐proteins in complex cellular extracts, [34] as well as for the postsynthetic labeling of oligonucleotides in fixed cells, [35] we envisaged to utilize sydnones instead of azides for imaging complex glycans in living mammalian cells [39] .…”
Section: Exploiting Sydnone 13‐dipoles As Chemical Reporters For Cont...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chinoy et al synthesized sialic acid derivatives with sydnones on either the C5 or N -acetyl position, termed Neu5SydCl and Neu9NSydCl respectively. 49 Interestingly, Neu5SydCl was not metabolically efficiently transferred on to protein substrates while Neu9NSydCl showed robust labeling. In addition, Neu9NSydCl could only be tolerated a few STs indicating that Neu9NSydCl labeling could differentiate among various types of sialosides.…”
Section: First Generation Mcrsmentioning
confidence: 99%
“…Currently, mesoionic compounds experience a veritable renaissance. As examples, the role of sydnones to serve as masked, cyclic dipolarophiles in [2+3]‐cycloadditions [1] has been significantly expanded by copper‐catalyzed [2] or metal‐free strain‐promoted click ring closure reactions [3] and applications as biologically active compounds, [4] bioorthogonal reporters, [5] imaging reagents, [6] and fluorogenic compounds [7] . Furthermore, they can be used for the in vitro bioconjugation of purified proteins [8] .…”
Section: Introductionmentioning
confidence: 99%